Про стійкість руху за Хіллом у задачі трьох тіл - Сосницький, С.П. (Український математичний журнал, 2008)
Рассмотрен частный случай задачи трех тел, когда масса одного из них значительно меньше массы каждого из двух других тел.
Исследована связь между устойчивой по Лагранжу парой массивных тел и устойчивостью по Хиллу системы всех трех тел.
Доказана теорема, устанавливающая в рассматриваемом случае существование устойчивых по Хиллу движений. Проведена аналогия с ограниченной задачей трех тел. Полученная теорема позволяет сделать вывод о существовании устойчивых по Хиллу движений в случае эллиптической ограниченной задачи трех тел. We consider a special case of the three-body problem, where the mass of one of these bodies is
considerably less than masses of other ones, and explore relations between the Lagrange stability of the
pair of massive bodies and the Hill stability of the whole system. We prove a theorem, which states the
existence of Hill stable motions in the three-body problem under consideration. Additionally, we
suggest an analogy with the restricted three-body problem. The obtained theorem implies that Hill stable
motions exist also in the case of the elliptic restricted three-body problem.